Synthesis of novel 2-alkyl substituted oleobenzimidazole derivatives using ethylene glycol as solvent - Hosamani, K. M.; Hiremath, V. B.; Keri, R. S.; Harisha, R. S.; Halligudi, Shivaraj B. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2008)
The objective of this research was to conduct constructive organic chemistry by using ethylene glycol as an efficient solvent and to achieve yields that were comparable to or better than those in other media. The reaction parameters, such as temperature (150-200 degrees C), density, and reaction time (6 h), have been systematically studied to understand whether ethylene glycol is as an efficient solvent and can have a positive effect on the chemistry with good yields. By tuning the parameters, the yields have been optimized to around 70%-80%. Thus, a new class of 2-alkyl substituted oleo-benzimidazole derivatives have been synthesized and characterized by FTIR, (1)H NMR, (13)C NMR, MS, and elemental analysis.
Keywords: ethylene glycol; oleo-benzimidazole derivatives; oleochemistry; unusual fatty acids